SOCCER, MEDIA AND VIOLENCE (Fiep Bulletin - online, 2013)
Violence in soccer has been a source of concern for professionals from diverse areas of knowledge, such as: Physical education, Psychology, Sociology, Public Security and Law. Considering that soccer is the most popular sport in Brazil and perhaps in the world, being part of the popular culture and occupies great spaces in the media, the objective of this study was to investigate the violence in sports, represented in this study by soccer, to locate it in the social context as subject explored by the media, as well as to identify aspects that contribute to extend or to minimize the violence in soccer. This is about a bibliographical study, in which situations of violence in soccer between athletes, controllers and supporters have been analyzed inside and outside the fields and the repercussion in the media. The film “Inacreditável - a Batalha dos Aflitos” was the object of analysis, and it portrays the events of a game with war-like characteristics, identified from the preparation of the field to the accomplishment of the match. In this game, factors were present which were pointed out by some authors as violence generators: Value of the match, opponent provocation, coach behavior, efficiency level of the team and score of the game. With the study it was possible to conclude that there is a fascination for any report on violence in general; in sports, it can be considered the violence of soccer and the violence in soccer, where people are influenced, as well as they tend to extend the effects of the violent facts spread in the media.
Keywords: soccer; media; violence